Novel action of FOXL2 as mediator of Col1a2 gene autoregulation - Marongiu, Mara; Deiana, Manila; Marcia, Loredana; Sbardellati, Andrea; Asunis, Isadora; Meloni, Alessandra; Angius, Andrea; Cusano, Roberto; Loi, Angela; Crobu, Francesca; Fotia, Giorgio; Cucca, Francesco; et al. (Developmental biology, 2016)
FOXL2 belongs to the evolutionarily conserved forkhead box (FOX) superfamily and is a master transcription factor in a spectrum of developmental pathways, including ovarian and eyelid development and bone, cartilage and uterine maturation. To analyse its action, we searched for proteins that interact with FOXL2. We found that FOXL2 interacts with specific C-terminal propeptides of several fibrillary collagens. Because these propeptides can participate in feedback regulation of collagen biosynthesis, we inferred that FOXL2 could thereby affect the transcription of the cognate collagen genes. Focusing on COL1A2, we found that FOXL2 indeed affects collagen synthesis, by binding to a DNA response element located about 65Kb upstream of this gene. According to our hypothesis we found that in Foxl2−/− mouse ovaries, Col1a2 was elevated from birth to adulthood. The extracellular matrix (ECM) compartmentalizes the ovary during folliculogenesis, (with type I, type III and type IV collagens as primary components), and ECM composition changes during the reproductive lifespan. In Foxl2−/− mouse ovaries, in addition to up-regulation of Col1a2, Col3a1, Col4a1 and fibronectin were also upregulated, while laminin expression was reduced. Thus, by regulating levels of extracellular matrix components, FOXL2 may contribute to both ovarian histogenesis and the fibrosis attendant on depletion of the follicle reserve during reproductive aging and menopause. •Forkhead transcription factor FOXL2 interacts with C-propeptides of COL1A2.•FOXL2 binds to a putative responsive element upstream of the Col1a2 gene.•FOXL2 binding to the target sequence activates a downstream Col1a2 promoter.•FOXL2 has a role in the dynamics of the ECM.•In Foxl2−/− mouse ovaries, Col1a2 is elevated from birth to adulthood.